Extinction: Hidden in plain sight: Can stories of 'the last' unearth environmental law's unspeakable truth? - LIM, Michelle Mei Ling (Institutional Knowledge at Singapore Management University, 2021)
Extinction. It is almost as though we dare not speak its name. Instead, words such as ‘threatened’ and ‘endangered’ are entrenched in conservation law and management as markers of risk. These terms are so entrenched that the nature of the risk is easily forgotten. On reflection, classifications of conservation status denote, of course, how close species are from disappearing forever. However, our familiarity with categories of biodiversity decline, the lack of explicit objectives to prevent avoidable extinctions within law and the failure of laws to directly tackle the drivers of biodiversity loss mean that the reality of extinction is ultimately buried in plain sight of the law. We need to change how extinction is seen and more importantly how it is felt within environmental law. An endling is the last of a kind. The final remaining individual of a plant or animal species. The paper explores the power and potential of endlings to illuminate the reality of extinction and our responsibilities to the more-than-human. Through stories of endlings past, recent and yet to come, the paper urges humans, and the legal instruments that encapsulate human values, to see and feel extinction and ultimately shift current extinction trajectories.